PENGARUH GAME BOARD TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN PADA ANAK USIA 4-5 TAHUN DI TK ISLAM FATIMAH KECAMATAN TAMPAN KOTA PEKANBARU - Munawaroh, Siti; Novianti, Ria; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on field observations, it can be seen that the ability to recognize the symbol of numbers in children aged 4-5 years has not developed optimally. So it is necessary to apply game board. This study aims to determine the effect of game board on the ability to recognize the symbol of numbers in children aged 4-5 years in Fatimah Islamic Kindergarten, Tampan District, Pekanbaru City. This study used an experimental method with one-group pretest-posttest design. The population in this study were children aged 4-5 years. The sample in this study was group A totaling 15 children. The data collection technique used is observation. The data analysis technique in this study used the t-test. The results of this research hypothesis test were obtained t = 11,635 with (Sig. 2- tailed) = 0.00 <0.05, which means that there was a significant increase after using the labyrinth game during the learning process. The influence given by the use of game board games on the ability to recognize the symbol of numbers in children aged 4-5 years in the Fatimah Islamic Kindergarten in Pekanbaru is 55.88% in the medium categoryKey Words: Board, Number Symbol